Ludificação da Realidade Virtual com Biofeedback para o Tratamento de Fobias Situacionais de Carácter Ambiental e Espacial - Luis Fernando Castro e Costa (2022)
The Virtual Reality (VR) gamification is an innovative and emerging paradigm. As an unconventional modality of therapy, in a VR environment linked to biofeedback, patients have the possibility to navigate and interact with situations similar to those of the disorder in question, in a gradual and controlled way. This resource allows health professionals to have access to a system where they can access the degrees of exposure to trauma through biofeedback, and contribute to the alleviation of anxiety motivated by the phobia. This dissertation intends to explore possibilities of virtual reality (VR) gamification and develop an exploratory prototype. The investigation will focus its study on situational phobias of an environmental and spatial nature, such as acrophobia.